2022
DOI: 10.1155/2022/6361098
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Maintenance and Management Technology of Medical Imaging Equipment Based on Deep Learning

Abstract: Medical equipment maintenance in modern hospital management is an emerging marginal discipline which is one of the important branches of hospital management with the dual function of management and technology. The good or bad management of medical equipment directly affects the quality of hospital work. With the development of science and technology, the scale of hospitals continues to expand and develop; hospitals are equipped with more and more medical equipment and its technical content is getting higher an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Between January 2019 and December 2020, a study was conducted involving 643 ‘LINAC down’ events, with equipment manufacturers also included as participants [ [14] , [15] , [16] ]. The inclusion criteria included the following: 1) LINAC faults, 2) the involvement of eight LINACs from three manufacturers, and 3) the application of varied improvement measures for different faults.…”
Section: Information and Methodologymentioning
confidence: 99%
“…Between January 2019 and December 2020, a study was conducted involving 643 ‘LINAC down’ events, with equipment manufacturers also included as participants [ [14] , [15] , [16] ]. The inclusion criteria included the following: 1) LINAC faults, 2) the involvement of eight LINACs from three manufacturers, and 3) the application of varied improvement measures for different faults.…”
Section: Information and Methodologymentioning
confidence: 99%
“…Some issues need to be further discussed and get into the solutions, so that the medical equipment in maintaining or replacing the process is well-managed. The issues faced in decision-making of medical equipment whether to maintain or replace were: (1) poor systematic mechanism in managing medical equipment Liu & Tong (2022); (2) medical equipment maintenance made based on its age only (Salim & Mazlan, 2019); (3) lack of sources from previous study Zamzam (2021); (4) the information required for making decisions differ according to organization level Rahman (2019); and (5) errors related to medical equipment occurred (Torkzad & Beheshtinia, 2019). Hence, the multi-criteria decision-making (MCDM) approach has been used to prioritize maintenance requirements for medical equipment and establish guidelines for choosing the right maintenance strategy (Bragazzi & Mansour, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%